AN IRANIAN CULTURAL APPROACH TO MANICHAEAN GNOSTICISM - Esmailpour, Abolqasem (Journal of Dharma, 2005)
The cultural origin of Manichaeism was first in Babylonia and Mesopotamia. Mani, although of an Iranian monarchy family, was nurtured in the Gnostic society of Babylonia. He was an expert intellectual and artist who had an undeniable and durable influence on Iranian culture through writing Gnostic works, paintings, calligraphy and tadhib ‘bookgilding’). Manichaeism and its religious-gnostic ideas, however, when reached the territory of Persia, naturally took on a Persian tincture. This can be clearly seen through the terms and the nomenclature of Manichaean deities such as Zurwān, Ohrmizdbay, Mihr Yazd, etc. One can see Iranian cultural influence on Manichaeism through its original themes and motifs and also through the functions of the deities. Zoroastrian dualistic doctrine and its impact on the Manichaean approach are undeniable. The specific functions of deities such as Zurwān and Mihr Yazd, and their reflections on Manichaeism are noticeable as well. In other words, the characteristics and functions of Zoroastrian deities match those of the Manichaean deities that were given their names. For instance, Zurwān, according to Iranian and Armenian sources, is a God of Time with an unlimited realm, who is the origin of Ohrmazd and Ahriman, twin gods of Good and Evil. In this way, Ohrmizdbay in Manichaean cosmogony is comparable with Zoroastrian Ohrmazd. The former is the symbol of forgetfulness and gaining knowledge to be redeemed, and he is the first deity to fight with Ahriman, while the latter is the Lord of knowledge and wisdom and is in conflict with Ahriman too.